2015
DOI: 10.4236/ojmh.2015.54009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Driving Force of Hydrodynamics in Lake Naivasha, Kenya

Abstract: The hydrodynamics in Lake Naivasha, a shallow endorheic lake, are simulated using the Delft3D Flow Module to investigate the major driving forces of hydrodynamics in the lake. The results showed wind as the major forcing. The shallow zones of the lake showed currents movement in the same direction as the wind while the deep zones showed currents movements against the wind direction. These findings were confirmed and further explained using an idealized model. Limited exchange between the Crescent Lake (crater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It was observed that sediment is almost evenly distributed within the lake over the past 20 years, compared with the 50‐year deposition pattern (Figures and ). According to Ndungu et al (), wind wave action varies in Lake Naivasha, being a phenomenon that can affect the sediment resuspension and redistribution. Sediment deposition patterns in a lake or reservoir also can change with time, sediment composition and biological mixing (Lehman, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that sediment is almost evenly distributed within the lake over the past 20 years, compared with the 50‐year deposition pattern (Figures and ). According to Ndungu et al (), wind wave action varies in Lake Naivasha, being a phenomenon that can affect the sediment resuspension and redistribution. Sediment deposition patterns in a lake or reservoir also can change with time, sediment composition and biological mixing (Lehman, ).…”
Section: Resultsmentioning
confidence: 99%
“…The northern part of the lake, with water depths varying between 1 and 3 m (Figure 4), could be an area in which sediment is continuously resuspended and redistributed by wave action, resulting to the area exhibiting less deposited sediment. Ndungu, Chen, Augustijn, and Hulscher (2015) observed that strong wave action, and current is experienced near the northern part of Lake Naivasha. The hydrodynamics of a lake, and the direction and strength of wind, influence where sediments are deposited within a given lake (Ndungu et al, 2015;Shotbolt et al, 2005).…”
Section: Sediment Thickness and Distribution In Lake Naivashamentioning
confidence: 99%
See 1 more Smart Citation
“…The Delft3D model, developed by Deltares, The Netherlands, was selected because of its versatility. The Delft3D model has been validated for different lakes worldwide, including Lake Victoria [32] and Navashi in Kenya [33], El-Burullus Lake in Egypt [34], Lake Ichkeul, Tunisia [35], Lake Tahu, China [23], Lake Geneva, Switzerland [36], and many lakes in The Netherlands [37].…”
Section: Introductionmentioning
confidence: 99%